Research of nitrogen-excretory function of kidneys in immature rats against the background of administration of new urolithic agent based on succinate under the conditions of experimental simulation of renal failure - Ermolenko, T. I.; Zupanets, I. A.; Otrishko, I. A. (Zaporozhye Medical Journal, 2013)
Presented results of the study of complex (Sc+PE) influence on the nitrogen-excretory kidney function at the conditions of experimental kidney insufficiency in young rats showed, that application of mentioned complex in 2,0 ml/kg dose produces more expressed positive effect on the indexes of the nitrogen-excretory function of kidneys in young rats than in the dose of 3,2 ml/kg, it is improved by increase of excretion of urea, creatinine, uric acid by the kidneys and decrease of their contents in the blood of animals. It was shown that these results completely correlate with the analogical indexes for sexually mature animals. This complex (Sc+PE) may be concidered as perspective nephroprotective and urolitholytic remedy for application in paediatrics.